(untitled) (Research, Society and Development, 2019)
This article has as main objective to analyze the Corporate Governance (CG) as a determinant of performance for the 27 Financial Institutions listed on the banking segment of Brasil, Bolsa, Balcão (B3) in 2018. Finding out, if these corporations obtained better indicators of profitability, liquidity and market by the fact of being members of the special levels of Corporate Governance (Level 1, Level 2 and New Market). According to Fernandes, Dias and Cunha (2010), and Vinhado (2010), the CG would diminish the agency conflicts that are maximized by the extra risk presented on this segment, and it would also increase their performances seeing the special levels are more burocratic. For analysis, the information were collected through the Balance Sheet, Income Statement, Cash Flow Statement and Explanatory Notes, from 2010 to 2017. All indicators were calculated and classified in two different groups: one with special Corporate Governance, and the other one without it. The hypothesis were tested using the t-Student test, checking if there is difference between the means of the two groups, in a confidence level of 95%. The results refused the hypothesis of that belonging to a Corporate Governance special level guarantees better liquidity and profitability indicators, with the exception of the Profit margin that is higher on this case. However, it was confirmed that companies in the CG special levels have better EBITDA. Therefore, it is concluded that financial and economic results of banking operations are not positively impacted by CG, as opposed to market performance.